The Bethlen Castle Garden in Keresd at the turn of the 20th century: An analysis of the historical pictures - Tăslăvan, Marius Róbert; Fekete, Albert; Surányi, Beáta Csilla; Komes, Dániel (4D Journal of Landscape Architecture and Garden Art, 2024)
The Bethlen Castle and Garden in Keresd represent oneof the most important heritage sites of the Transylvanian Renaissance. The landscape garden and its historicising garden elements from the 18thand 19th centuries are preserved partially on this site. Evidence from contemporary archival sources, records, photographs, field artifacts and oral accounts from witnesses appears to providea clear picture of the garden's previous state. The authors of this study have been engaged in researching the garden's history in recent years, both in the context of a thesis and a garden history study. This paper will apply the research findings to present a comprehensive history of Keresd Castle Garden, highlighting its significance during a specific time period spanning a few decades. This work is based primarily on research and analysis of descriptive historical sources, historical maps, artistic representations and historical photographs. The historical research is enhanced by on-site surveys, along with the findings from archaeological excavations and geophysical measurements in particular sections of the garden. The inventories and censuses, official correspondence and economic documents found in the archives clearly show the outstanding historical value and importance of the site in Transylvania, mainly due to the prestigious position and political and economic connections of the Bethlen family. The research aims to identify defining garden features from the late 1800s-early 1900s, to help determine thesite's heritage value and guide future garden renovations.
Keywords: Transylvanian Renaissance; landscape garden; philagoria; garden pond; historicising garden elements